Green Remediation of Used Cooking Oil Using Sugarcane Bagasse: A Sustainable, Green Chemistry Approach - Mirah Surya Dewi, Ni Pt. Pande; Khodizah, Ayu Tri (Journal of Mathematics Science and Computer Education, 2024)
Environmental pillars are the foundation of sustainable development, emphasizing waste management solutions like used cooking oil purification. This study assesses used cooking oil quality based on color, odor, water content, free fatty acids, and peroxide value after sugarcane bagasse adsorption over 1, 2, and 3 days. Using a one-group pretest-posttest design, the 3-day treatment yielded optimal results: peroxide value (5.603 meq/kg), water content (0.070%), and free fatty acids (0.13%) decreased significantly, with improved color and odor compared to the control. The study integrates green chemistry principles, including waste prevention, energy efficiency, renewable material use, chemical degradation design, and safer chemical applications. This minimizes hazardous material usage, energy consumption, and environmental impact. Spent bagasse can be transformed into valuable products like compost or biofuel, providing sustainable solutions for managing used cooking oil waste, while reducing pollution and greenhouse gas emissions. The research offers an effective strategy aligned with Indonesia's conservation goals and green chemistry principles. It encourages public participation in local waste management, potentially inspiring innovative approaches for handling other waste types, thereby strengthening sustainability efforts.